Enhancing the sense of togetherness among youth via Facebook: a case study on 1Malaysia Wireless Village Project - Sahharon, Hamizah; Bolong, Jusang; Omar, Siti Zobidah (Universiti Putra Malaysia Press, 2018)
This paper explores some topics related to enhancing the sense of togetherness among youth within a virtual community. With the wider use of the Internet among the rural youth in Malaysia, rural communities are more exposed to global connection. The 1Malaysia Wireless Village Project has taken this many steps forward. The Internet has occupied social media of all kinds, and social media are widely accessed among rural youths. Rural youths occupy themselves within the social space of Facebook in a way that suggests that they find its functions useful for staying connected with friends near and far. Primary analysis has found that use of Facebook functions creates not only a social bond and support but also builds a social channel for obtaining and sharing current issues among virtual group members. The frequent use of its specific functions such as conversation, sharing, identity, reputation and group were found to have significant correlation with users' sense of togetherness. However, it was identified that the frequent use of the group function contributed the most to enhancing the perceived sense of togetherness among the virtual community members.